Multimedia Integration in Science Instruction: Proficiency Training Plan - Rowena B. Lascoña; Rufino T. Tudlasan Jr (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study assessed the extent of multimedia integration among science teachers of Bayongan Elementary School, San Miguel District, Division of Bohol for the School Year 2025–2026. Specifically, it examined the teachers’ demographic and professional profiles—including age, gender, civil status, educational attainment, years of service, and related trainings—as well as the learners’ age and gender. The study also determined the extent of teachers’ utilization of multimedia instructional tools in terms of text, graphic, audio, video, and interactive media, and explored their perceptions of multimedia integration in the instructional, communication, organizational, analytical, and expansive domains. A descriptive–correlational research design was employed using an adapted and modified questionnaire as the main data-gathering instrument. Findings revealed that most teachers were female, aged 41–50 years, married, bachelor’s degree holders, with 16–20 years of teaching experience, and had attended division-level trainings. The majority of learners were 10 years old and female. Results showed that multimedia instructional tools were utilized to a great extent, with audio and graphic tools being the most frequently used, followed by text, video, and interactive media. Teachers demonstrated positive perceptions toward multimedia integration, recognizing its effectiveness in enhancing instruction, communication, organization, and analytical and expansive thinking skills. A significant correlation was found between the extent of multimedia integration and learners’ proficiency in science. Challenges identified included limited access to technology, inadequate teacher training, technical issues, time constraints, inequities, maintenance and sustainability concerns, poor internet connectivity, teacher resistance, assessment difficulties, and student distractions. The study concludes that greater multimedia integration is significantly associated with higher learner proficiency in science. It is recommended that a multimedia digital training plan be implemented in School Year 2026–2027 to further strengthen teachers’ capacity for effective multimedia integration.